Contamination of Proteus mirabilis harbouring various clinically important antimicrobial resistance genes in retail meat and aquatic products from food markets in China - Ma, Wan-Qing; Han, Ying-Yue; Zhou, Lin; Peng, Wen-Qi; Mao, Ling-Ya; Yang, Xue; Wang, Qin; Zhang, Tie-Jun; Wang, Hong-Ning; Lei, Chang-Wei (Frontiers in Microbiology, 2022)
Proteus mirabilis is an opportunistic pathogen frequently associated with nosocomial infection and food poisoning cases. Contamination of P. mirabilis in retail meat products may be important transmission routes for human infection with P. mirabilis. In this study a total of 89 P. mirabilis strains were isolated from 347 samples in 14 food markets in China and subjected to whole-genome sequencing. Phylogenetic analysis showed that all 89 strains were divided into 81 different clones (SNPs >5), indicating high genetic diversity of P. mirabilis in food markets. Antimicrobial susceptibility testing showed that 81 (91.01%) strains displayed multidrug resistance profiles. Seventy-three different resistance genes (or variants) were found, including various clinically important antimicrobial resistance genes aac(6′)-Ib-cr (77.53%), blaCTX-M (39.33%), fosA3 (30.34%), as well as multiresistance gene cfr (4.50%), tigecycline resistance gene cluster tmexCD3-toprJ1 (4.50%) and carbapenemase gene blaNDM-1 (1.12%). Diverse genetic elements including Tn7 transposon, plasmid, SXT/R391 integrative conjugative element were associated with the horizontal transfer of cfr. tmexCD3-toprJ1 and blaNDM-1 were located on ICEPmiChnJZ26 and Salmonella genomic island 1, respectively. Our study emphasized high contamination of P. mirabilis harbouring various clinically important antimicrobial resistance genes in retail meat and aquatic products, which might be an important issue in terms of food safety and human health.